Herpes Simplex Virus Type 2 Functions Expressed During Stimulation of Human Cell DNA Synthesis - Kucera, Louis S. (1979)
Experiments were designed to identify herpes simplex virus type 2 (HSV-2)-specific functions expressed during stimulation of human embryo fibroblast DNA synthesis. Cultures were partially arrested in DNA synthesis by pretreatment with 5-fluorouracil and maintenance in low-serum (0.2%) medium during virus infection. Results showed that continuous [methyl-(3)H]thymidine uptake into cellular DNA was ninefold greater in HSV-2-infected than in mock-infected cultures measured after 24 h of incubation at 42°C. Shifting mock-infected cultures from low- to high-serum (10%) medium also caused some stimulation, but [methyl-(3)H]thymidine uptake was only twofold greater than in cells maintained with low serum. Plating efficiencies of both HSV-2-infected and mock-infected cells at 42°C were essentially the same and ranged from 37 to 76% between zero time and 72 h of incubation. De novo RNA and protein syntheses were continuously required for HSV-2 stimulation of cellular DNA synthesis. HSV-2 infection markedly enhanced transport, phosphorylation, and rate of incorporation of [methyl-(3)H]thymidine into cellular DNA, starting at 3 h and reaching a maximum by 12 h; after 12 h, these processes gradually declined to low levels. In mock-infected cells these processes remained at low levels throughout the observation period. Pretreatment of cells with interferon or addition of arabinofuranosylthymine at the time of virus infection inhibited stimulation caused by HSV-2. 5-Bromodeoxyuridine density-labeled experiments revealed that HSV-2 stimulates predominantly semiconservative DNA replication and some DNA repair. Stimulation of [methyl-(3)H]thymidine into cellular DNA correlated with detection of virus-specific thymidine kinase activity. In conclusion, HSV-2 stimulation of cellular DNA synthesis appeared to involve at least four virus-specific functions: induction of thymidine transport, HSV-2 thymidine kinase activity, semiconservative replication, and repair of cellular DNA.